2015
DOI: 10.1021/acs.bioconjchem.5b00352
|View full text |Cite
|
Sign up to set email alerts
|

Critical Effect of Base Pairing of Target Pyrimidine on the Interstrand Photo-Cross-Linking of DNA via 3-Cyanovinylcarbazole Nucleoside

Abstract: To evaluate the effect of base pairing of the target pyrimidine on the interstrand photo-cross-linking reaction of DNA via 3-cyanovinylcarbazole nucleoside ((CNV)K), a complementary base of target pyrimidine was substituted with noncanonical purine bases or 1,3-propandiol (S). As the decrease of the hydrogen bonds in the base pairing of target C accelerated the photo-cross-linking reaction markedly (3.6- to 7.7-fold), it can be concluded that the number of hydrogen bonds in the base pairing, i.e., the stabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…10 μM photo-cross-linked dsDNA was analyzed with HPLC system; elution was with 0.05 M ammonium formate containing 98–50% CH 3 CN, linear gradient (60 min) at flow rate of 1 mL/min. 4-Acetylpyridine, Aniline, Acetanilide, Phenol, Benzonitrile and Acetophenone were used as control compound to create calibration curve [ 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 μM photo-cross-linked dsDNA was analyzed with HPLC system; elution was with 0.05 M ammonium formate containing 98–50% CH 3 CN, linear gradient (60 min) at flow rate of 1 mL/min. 4-Acetylpyridine, Aniline, Acetanilide, Phenol, Benzonitrile and Acetophenone were used as control compound to create calibration curve [ 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…In 2015, we showed the effect of hydrogen bonding on the rate of the photo-cross-linking reaction by changing the counter-base of cytosine [ 26 ], which led to the idea that hydrogen bonding could also play a role in the deamination reaction. In 2017, we further proved our hypothesis by showing that certain counter-bases, especially inosine, of cytosine are better for deamination than other bases due to a specific type of hydrogen bonding in the cross-linked cytosine [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] Recently, Fujimoto et al have described a crosslinking-assisted SNP genotyping, showing the potential of photo-crosslinks for biological applications. [7] In a more therapeutic context, it was extensively reported that blocking single stranded mRNA sequences through hybridization with their antisense complement leads to inhibition of expression and thus inhibition of the synthesis of the corresponding proteins. [8] Recently, various research groups have demonstrated that by introducing an ICL between a mRNA sequence and its antisense complement, the inhibitory effect becomes even more distinct.…”
Section: Introductionmentioning
confidence: 99%